A Structural Error Analysis of Abstracts of Undergraduate Research Reports - Asteria Ngaiza (UNIB Press, 2023)
The competence level of language users can be analysed through error analysis. This study sought to understand the level at which undergraduate students at the Moshi Co-operative University in Tanzania have attained English language competence through error analysis. The study collected 60 abstracts from three bachelor degree programs pursued at the University. The study used qualitative research design and error analysis theory to identify, group and describe errors. The findings revealed that students are prone to errors. The most problematic ones include fragment and dangling modifier errors, wrong usage of definite and indefinite errors and fused sentence errors. Some of the apparent errors that students made were punctuation errors; these were made of negligence since the learners could have minimised them through their tutors' interventions. This study urges the tutors of these students to help correct these obvious errors as there could be long-term negligence among these learners, negatively impacting their English language competence. This study urges teachers to devise teaching strategies to minimise errors students commit when learning a second language.